Light Metals 2019 - Chesonis, Corleen (The Minerals, Metals & Materials Series,, 2019)
The Light Metals symposia at the TMS Annual Meeting & Exhibition present the most recent developments, discoveries, and practices in primary aluminum science and technology. The annual Light Metals volume has become the definitive reference in the field of aluminum production and related light metal technologies. The 2019 collection includes papers from the following symposia: 1. Alumina and Bauxite 2. Aluminum Alloys, Processing, and Characterization 3. Aluminum Reduction Technology 4. Cast Shop Technology 5. Cast Shop Technology: Energy Joint Session 6. DGM-TMS Symposium on Lightweight Metals 7. Electrode Technology for Aluminum Production 8. REWAS 2019: Cast Shop Recycling Technologies 9. Scandium Extraction and Use in Aluminum Alloys 10. Ultrasonic Processing of Liquid and Solidifying Alloys.